Minha Casa Minha Vida, além da casa: política habitacional e infraestrutura dos equipamentos públicos em Feira de Santana - Oliveira, Nathalia Santos (2023)
This dissertation aimed to evaluate the demands of public facilities that serve as support for the residents of Residencial Viver Alto do Rosário, an enterprise made possible by the Minha Casa Minha Vida Program (PMCMV). Throughout the research, a brief historical context about housing policies was presented. from the 1930s to the year 2009 when the PMCMV was launched, as well as the presentation of the program in the city of Feira de Santana - Bahia. The largest residential range 1 of the program in the Northeast. During the work carried out, it is verified that the public facilities studied - school, day care center and health unit - which are in the vicinity of the project, do not have the necessary conditions to meet the needs of the residents, directly impacting their quality of life. The investigation was carried out through visits to the residential and equipments selected and interviews with social subjects, seeking answers about the investigated reality. It was concluded that despite the commitment of professionals and the community, and community leaders to seek improvements in the quality of services provided, the demands are still latent and have not been met, making each day a challenge to be overcome while await the effectiveness of society's rights